Kajian Hukum Atas Radikalisme Pada Aparat Sipil Negara (ASN) Di Indonesia - Asianto Nugroho; sapto Hermawan (Cakrawala Hukum: Majalah Ilmiah Fakultas Hukum Universitas Wijayakusuma, 2020)
The potential of radicalism distribution is quite alarming. This understanding of radicalism targets all elements of the nation, including the Government Officer (ASN). As part of the government, ASN which is exposed to radicalism is considered dangerous to the establishment of the 1945 Constitution of the Republic of Indonesia and the ideology of Pancasila which is the basic norm for the establishment of the Republic of Indonesia. This article aims to find out (1) supervision of ASN in order to prevent radicalism if compared from the perspective of staffing regulations; and (2) legal sanctions that can be given to ASN who have been exposed to radicalism. This article was written using the normative legal research. Secondary data sourced from literature review which is then qualified and quarantined to answer the problem formulation. The results showed that the Government had conducted a movement involving 11 Ministries and State Institutions as a Joint Task Force to anticipate violations of the Government Officer radicalism. Based on the Joint Decree which contains 11 points to identify ASN as an online measurement benchmark supported by facts and reality in the ASN complaint portal, so as to create comfort for ASN extended family and improve Key Performance Indicators throughout ASN in Indonesia.Keywords: Radicalism, the Government Officer, Oversight and Sanctions.Â Abstrak. Potensi sebaran paham radikalisme cukup mengkhawatirkan. Paham radikalisme ini menyasar kesemua elemen bangsa, termasuk di dalamnya adalah Aparatur Sipil Negara (ASN). Sebagai bagian dari pemerintahan, ASN yang terpapar paham radikalisme dinilai membahayakan tegaknya Konstitusi Undang-Undang Dasar Negara Republik Indonesia 1945 dan ideologi Pancasila yang menjadi norma dasar berdirinya Negara Kesatuan Republik Indonesia. Artikel ini bertujuan untuk mengetahui (1) pengawasan terhadap ASN guna mencegah radikalisme jika dikomparasikan dari perspektif regulasi kepegawaian; dan (2) sanksi hukum yang dapat diberikan kepada ASN yang telah terpapar paham radikalisme. Artikel ini ditulis menggunakan metode penelitian hukum normative. Data sekunder bersumber dari kajian pustaka yang kemudian dikualifikasi dan dikuantisir untuk menjawab rumusan masalah yang ada. Hasil penelitian menunjukan bahwa Pemerintah telah melakukan gerakan yang melibatkan 11 Kementrian dan Kelembagaan Negara sebagai Satuan Tugas bersama untuk mengantisipasi terjadinya pelanggaran radikalisme ASN. Berdasarkan Surat Keputusan Bersama yang berisi 11 poin poin guna mengidentifikasi ASN sebagai tolok ukur aduan secara on line yang didukung fakta dan realita dalam portal aduan ASN, sehingga tercipta kenyamanan keluarga besar ASN dan meningkatkan Key Performance Indicator seluruh ASN di Indonesia.Kata Kunci: Radikalisme, Aparat Sipil Negara, Pengawasan dan Sanksi